ASPEK BIOLOGI DAN ABLASI MATA PADA UDANG WINDU Penaeus monodon SUKU PENAEIDAE (DECAPODA: MALACOSTRACA) - Rianta Pratiwi (Pusat Penelitian Oseanografi LIPI, 2018)
THE ASPECTS OF BIOLOGY ANDEYE ABLATION ON SHRIMP Penaeus monodon PENAEIDAE (DECAPODA: MALACOSTRACA). A qood quality of seeds (fry) is a very important production component to support the shrimp farming activities in ponds. The quantity and quality of shrimp seeds are largely determined by hatchery products obtained from the quality of the broodstock used. The provision of the broodstock is the beginning of the seed production activities and is one of the factors that determines the quality and quantity of the production. The growing demand for mature gonad shrimp is a big problem for shrimp farmers, due to the ability of windu shrimp to spawn in the nature (ripe gonad naturally) takes relatively long time. Therefore, the eye ablation process can accelerate the process of gonad maturity. This article describes some aspects that should be understood in conducting windu shrimp farming as well as explanations of ablation process.